Progress in the detection and quantification of collagens: a review - Gameil, Abeir Hussein Mohamed; Yusof, Faridah; Azmi, Azlin Suhaida; Mohamad Puad, Noor Illi (IOP Publishing, 2021)
Collagens are an important and ubiquitous family of proteins. They have many functions in the human body and similarly have found numerous, potent applications in various industries including the manufacture of biomaterials. The ever-increasing demand for collagen has made necessary the exploration of alternative sources such as bacterial collagen-like proteins which have a triple-helical domain of Gly-X-Y amino acid repeats. Detection and quantification of native collagens have been well-established. However, collagen-like proteins differ in their composition and do not have the unique abundance of hydroxyproline and hydroxylysine found in vertebrate collagens. Thus, this poses a problem in the detection and quantification of collagenlike proteins. This paper evaluates reports on the detection and quantification of collagens and collagen-like proteins. A systematic search of the PubMed database was conducted in May 2021, to which five additional papers were added. The 310 unique search results were then subjected to a screening and elimination process, at the end of which 22 papers were included in the study. The findings were summarized and presented in a table that highlights progress in this field. While novel methods have been developed for the detection and quantitation of collagens in general, mainly using enzyme digestion, hybridization, and fluorescence, there is a need for a rapid, one-step method that selectively and sensitively detects and quantitates collagen and collagen-like protein samples with ease.